mRNA expression profiles in muscle-derived extracellular vesicles of Large White and wild boar piglets reveal their potential roles in immunity and muscle phenotype - Yu, Naixiang; Chang, Xiaolong; Hu, Jianchao; Li, Jianjun; Ma, Junwu; Huang, Lusheng (Frontiers in Veterinary Science, 2024)
IntroductionExtracellular vesicles (EVs) known for their pivotal role in intercellular communication through RNA delivery, hold paramount implications for understanding muscle phenotypic variations in diverse pig breeds.MethodsIn this study, we compared the mRNA expression profiles of longissimus dorsi muscles and muscle-derived extracellular vesicles (M-EVs), and also examined the diversity of enriched genes in M-EVs between weaned wild boars and commercial Large White pigs with respect to their numbers and biological functions.ResultsThe results of the study showed that the variation in the expression profiles of mRNAs between muscles and M-EVs was much greater than the variability between the respective breeds. Meanwhile, the enrichment trend of low-expressed genes (ranked <1,000) was significantly (p-value ≤ 0.05) powerful in M-EVs compared to highly expressed genes in muscles. In addition, M-EVs carried a smaller proportion of coding sequences and a larger proportion of untranslated region sequences compared to muscles. There were 2,110 genes enriched in M-EVs (MEGs) in Large White pigs and 2,322 MEGs in wild boars, with 1,490 MEGs shared interbreeds including cyclin D2 (CCND2), which inhibits myogenic differentiation. Of the 89 KEGG pathways that were significantly enriched (p-value ≤ 0.05) for these MEGs, 13 unique to Large White pigs were mainly related to immunity, 27 unique to wild boars were functionally diverse but included cell fate regulation such as the Notch signaling pathway and the TGF-beta signaling pathway, and 49 were common to both breeds were also functionally complex but partially related to innate immunity, such as the Complement and coagulation cascades and the Fc gamma R-mediated phagocytosis.DiscussionThese findings suggest that mRNAs in M-EVs have the potential to serve as indicators of muscle phenotype differences between the two pig breeds, highlighting the need for further exploration into the role of EV-RNAs in pig phenotype formation.